Cultural Continuity or Change: Pedagogical Implications of Layered Transformation in Malay Offering Dance - Silvia Gea; Agustina Agustina (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Urbanization and the growth of the creative industry have shifted the Riau Malay Offering Dance (Tari Persembahan) from sacred ceremonial contexts to commercial performance stages. While this transformation is often framed as a loss of tradition, limited attention has been given to its pedagogical implications—particularly how teachers transmit core values such as rasa (sensibility) and adab (politeness) in increasingly fast-paced and spectacular performances. This study employs a qualitative case study at Sanggar Wan Dance, Pekanbaru, and analyzes the transformation through the lens of deterritorialization. The findings reveal a layered transformation: the outer layer (costume and music) undergoes significant modification, the middle layer (movement structure) is simplified and accelerated, while the inner core (sembah gesture and ethical values) remains relatively stable. These results suggest that cultural preservation in contemporary contexts depends on intentional pedagogical design, where teachers actively implement explicit strategies to sustain and transmit core cultural values.